Asian Journal of Sustainability and Social Responsibility - Kim, Jong Dae
Asian Journal of Sustainability and Social Responsibility (AJSSR) provides a platform for research articles on Corporate Social Responsibility and Sustainability Development/Management issues specific to the Asian region. In particular, AJSSR values research that helps the audience develop a better conceptual base for understanding sustainability and social responsibility of organizations in the Asian region which have recently paid more attention to these topics than previously.